As singularidades cênicas do litoral paranaense : um olhar sobre a paisagem cultural de Guaraqueçaba/PR - Souza, Roberson Miranda de (2014)
The Guaraqueçaba city is located in Paraná state, on the coastal plain, at the region metropolitan of Paranaguá. Guaraqueçaba is a historic landmark, because it is among the first occupations by Portuguese settlers existing in Paraná state. It is one of the best preserved areas of Atlantic forest all over the country. The theme to be discussed consists in the evaluate on of the singularity of the cultural landscape, in short, the single character of the city and, due to this fact, the necessity to preserve it. Emphasizing the scenic landscapes, an evident scenic beauty related to its harmony in the traits and forms. The cultural landscape, in focus, has representativity because it is related to the material record of the start of construction of the Brazilian territory. It has a tourist expression, thus becoming a character landscape, which distinguishes the municipality, placing it in a select group of Paraná historic cities. The entire discussion is about preserving the landscapes, it happens in consequence of the strong existence of environment issue at the city. In the whole work around this thesis, the intellectual and material exercises are developed with the intention to understand the personality from Guaraqueçaba's landscape and assign it a score according to its attributes and material culture. Complementarily, to select the scenic landscapes and analyze the legibility of the urban landscape. Procedures and actions seek to work in getting the perspective of residents, former residents and tourists. The attempt was to merge the methodological naturalist model used by M. Passos, based on G. Bertrand by the way of working with the cultural landscape of H. Yamaki techer. The proposed methodology consists in the definition and evaluation of visual components and landscape attributes, thus: a) Guaraqueçaba starting from the bay; b) the bay starting from Guaraqueçaba; c) the urban landscape along the pier and the road; d) landscape features' identification; that allow, recognize Guaraqueçaba. The discussion about the scenic and urban landscape are complementary. The visual analysis contemplates the place, that's in the first plane, and the incursions which have a wide reach often beyond the visual. To determine the landscape character, we take into account its attributes. What are the landscape attributes? They are the ones that change and influence in the sets of elements. The issues surrounding the paving of road PR - 405 are analyzed, even the consequences that can be foreseen and avoided to maintain the scenic landscapes, and the most important, the rational utilization from this landscaping potential.